2015
DOI: 10.1177/0003489415574513
|View full text |Cite
|
Sign up to set email alerts
|

Novel ABHD12 Mutations in PHARC Patients

Abstract: This study shows that PHARC has phenotypic variability, even within a family, which is consistent with previous reports. Differential diagnosis of "deaf-blindness" diseases is crucial. Confirming the presence of associated symptoms is necessary for differentiating some deaf-blindness syndromes. In addition, mutation analysis is a useful tool for confirming the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
(15 reference statements)
1
13
0
Order By: Relevance
“…When ABHD12 activity is absent, the Purkinje neurons are constantly stimulated by the accumulated lyso-PS, resulting in deregulated cerebellar function [19]. Consistent with previous studies, we found that hearing loss was present in the majority of patients in childhood/early adolescence [1,10,20,21]. To date, it remains unclear where ABHD12 localizes and interacts in the inner ear, which is crucial for determining the cause of hearing loss in patients with PHARC syndrome.…”
Section: Discussionsupporting
confidence: 89%
“…When ABHD12 activity is absent, the Purkinje neurons are constantly stimulated by the accumulated lyso-PS, resulting in deregulated cerebellar function [19]. Consistent with previous studies, we found that hearing loss was present in the majority of patients in childhood/early adolescence [1,10,20,21]. To date, it remains unclear where ABHD12 localizes and interacts in the inner ear, which is crucial for determining the cause of hearing loss in patients with PHARC syndrome.…”
Section: Discussionsupporting
confidence: 89%
“…Mutations of ABHD12 have been reported in PHARC syndrome, which is characterized by a combination of polyneuropathy, hearing loss, ataxia, retinitis pigmentosa, and earlyonset cataracts. However, several biallelic pathogenic variants have been identified in patients clinically diagnosed with USH3-like symptoms or an autosomal recessive nonsyndromic form of retinal degeneration (Eisenberger et al 2012;Nishiguchi et al 2014;Sun et al 2018;Yoshimura et al 2015). One major problem with these studies is that they do not usually include neurological results for the patients, potentially leading to the misdiagnosis of their condition as USH3.…”
Section: Hars (Histidyl-trna Synthetase)mentioning
confidence: 99%
“…Its substrates include endocannabinoid transmitter 2-arachidonylglycerol (2-AG) and signaling lipids (lysophosphatidylserines, LPS) (83,114). Both Eisenberger et al and Yoshimura et al identified bi-allelic ABHD12 pathogenic variants in patients initially presenting with USH3-like symptoms (49,57). However, it is important to note that both sets of authors ultimately diagnosed the patients with a different condition comprising polyneuropathy, hearing loss, ataxia, retinitis pigmentosa, and early-onset cataract (PHARC).…”
Section: Ultra-rare Ush Genesmentioning
confidence: 99%